(2x +3) (x - 2) - 2x (x - 3) = 24
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(-6x^4+4x^3-2x^2\)
2) \(=x^2+4x-21-x^2-4x+5=-16\)
3) \(=6x^2-4x-x^2-4x-4=5x^2-8x-4\)
4) \(=2x^3-4x^2-8x-3x^2+6x+12=2x^3-7x^2-2x+12\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\left(x+1\right)^3+\left(x-2\right)^3=2x^3+2\left(2x-1\right)^2-9\)
\(\Leftrightarrow x^3+3x^2+3x+1+x^3-6x^2+12x-8=2x^3+2\left(4x^2-4x+1\right)-9\)
\(\Leftrightarrow2x^3-3x^2+15x-7=2x^3+8x^2-8x-7\)
\(\Leftrightarrow-11x^2+23x=0\)
\(\Leftrightarrow x\left(-11x+23\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{23}{11}\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(=6x^2+2x-15x-5-x^2+6x-9+4x^2+20x+25-27x^3-27x^2-9x-1\)
=-27x^3-18x^2+4x+10
2: =4x^2-1-6x^2-9x+4x+6-x^3+3x^2-3x+1+8x^3+36x^2+54x+27
=7x^3+37x^2+46x+33
5:
\(=25x^2-1-x^3-27-4x^2-16x-16-9x^2+24x-16+\left(2x-5\right)^3\)
\(=8x^3-60x^2+150-125+12x^2-x^3+8x-60\)
=7x^3-48x^2+8x-35
![](https://rs.olm.vn/images/avt/0.png?1311)
1) Ta có: \(\left(x+2\right)^2+\left(x-3\right)^2\)
\(=x^2+4x+4+x^2-6x+9\)
\(=2x^2-2x+13\)
2) Ta có: \(\left(4-x\right)^2-\left(x-3\right)^2\)
\(=\left(4-x-x+3\right)\left(4-x+x-3\right)\)
\(=-2x+7\)
3) Ta có: \(\left(x-5\right)\left(x+5\right)-\left(x+5\right)^2\)
\(=x^2-25-x^2-10x-25\)
=-10x-50
4) Ta có: \(\left(x-3\right)^2-\left(x-4\right)\left(x+4\right)\)
\(=x^2-6x+9-x^2+16\)
=-6x+25
5) Ta có: \(\left(y^2-6y+9\right)-\left(y-3\right)^2\)
\(=y^2-6y+9-y^2+6y-9\)
=0
6) Ta có: \(\left(2x+3\right)^2-\left(2x-3\right)\left(2x+3\right)\)
\(=4x^2+12x+9-4x^2+9\)
=12x+18
![](https://rs.olm.vn/images/avt/0.png?1311)
2: Để \(2x\left(x+1\right)< 0\) thì \(\left\{{}\begin{matrix}x+1\ge0\\x\le0\end{matrix}\right.\Leftrightarrow-1\le x\le0\)
Bạn ơi nếu x ≤ 0 mà x = 0 thì 2x (x+1) = 0
mà 0 = 0 thì sia rồi đúng ko
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{x\left(x^2+x-2\right)}{x+2}=\dfrac{x\left(x+2\right)\left(x-1\right)}{x+2}=x^2-x\)
b: \(=\dfrac{x^3-3x^2+2x+24}{x+2}=\dfrac{x^3+2x^2-5x^2-10x+12x+24}{x+2}=x^2-5x+12\)
\(\left(2x+3\right)\left(x-2\right)-2x\left(x-3\right)=24\)
\(\Leftrightarrow2x^2-x-6-\left(2x^2-6x\right)=24\)
\(\Leftrightarrow5x=30\)
\(\Leftrightarrow x=6\).